2018
DOI: 10.15649/cuidarte.v9i3.574
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da laserterapia no tratamento de lesões por pressão: uma revisão sistemática

Abstract: Efeitos da laserterapia no tratamento de lesões por pressão: uma revisão sistemática Effects of laser therapy in the treatment of pressure injuries: a systematic review Efectos de la laserterapia en el tratamiento de lesiones por presión: una revisión sistemática

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
10
Order By: Relevance
“…LLLT is a non-invasive therapy in which light beams are absorbed by epithelial tissues, acting on biostimulation directly on mitochondria, causing them to produce more ATP and lower oxygen consumption. In addition to the already mentioned effects, it promotes the elevation of serotonin and endorphin levels and decreases those of prostaglandin and interleukin beta, reducing pain 39 .…”
Section: Effects Of Photobiomodulation On Pain Reductionmentioning
confidence: 98%
See 1 more Smart Citation
“…LLLT is a non-invasive therapy in which light beams are absorbed by epithelial tissues, acting on biostimulation directly on mitochondria, causing them to produce more ATP and lower oxygen consumption. In addition to the already mentioned effects, it promotes the elevation of serotonin and endorphin levels and decreases those of prostaglandin and interleukin beta, reducing pain 39 .…”
Section: Effects Of Photobiomodulation On Pain Reductionmentioning
confidence: 98%
“…When there is some injury, these ATP levels are reduced. Still, biostimulation improves its synthesis, promoting increased nutrients and oxygen at the site, increasing tissue energy and, therefore, increasing cell division, enhancing the healing process 39,40 .…”
Section: Effects Of Photobiomodulation On Wound Healingmentioning
confidence: 99%
“…13 A study identified that health professionals, even those with qualifications to operate LASERs, have doubts regarding the dosage, wavelength, time, and number of applications to be used. 14 Therefore, it is important that health professionals, especially wound experts, understand the new approach of PDT in treating infected ulcers and incorporate it into their practice to promote optimized healing and reduce the number of complications due to DFU. 1,15 The study is relevant in combining the effects and protocols of DFU as an adjuvant therapy in infection reduction, optimizing DFU healing, and offering scientific evidence to reduce bacterial resistance and amputations.…”
Section: Introductionmentioning
confidence: 99%
“…O termo laser é um acrônimo da expressão em inglês Light Amplification by Stimulated Emission of Radiation, que significa a luz amplificada com a emissão estimulada de radiação. Como características físicas, a luz do laser é uma radiação eletromagnética, unidirecional e monocromática capaz de transmitir pacotes de energia denominado fótons (De Oliveira Bernardes & Regina Jurado, 2018;Diógenes Alves Uchôa Lins et al, 2010;Ferreira et al, 2021).…”
Section: Introductionunclassified